Utilization of the Facebook Marketplace as a Marketing Media and Promotional Media in Improving the MSME Economy of Pottery Pot Crafts in Kemangsen Village - Nefrida Jandini; Poppy Febriana; Moh Ar Raafi Ahsa Febian; Muhammad Rafli Sadar Darmawan Siahaan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This community service is entitled